2000
DOI: 10.1053/ejvs.2000.1151
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Level of Matrix Metalloproteinase 9 may Predict the Natural History of Small Abdominal Aortic Aneurysms. A Preliminary Study

Abstract: P-MMP9 and P-alpha 1 antitrypsin may predict the natural history of AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
95
3
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(117 citation statements)
references
References 30 publications
9
95
3
10
Order By: Relevance
“…Significant correlations with expansion were found in 2 studies (1 low and 1 medium bias risk; r =0.55 and r =0.42) with 61 follow‐up patients in total,10, 39 whereas 2 studies (1 low and 1 medium bias risk) could not reproduce such significant correlations in 66 follow‐up patients 18, 40. Pulinx et al, however, did reach significance when initial AAA diameter was included in their multivariate model 40…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Significant correlations with expansion were found in 2 studies (1 low and 1 medium bias risk; r =0.55 and r =0.42) with 61 follow‐up patients in total,10, 39 whereas 2 studies (1 low and 1 medium bias risk) could not reproduce such significant correlations in 66 follow‐up patients 18, 40. Pulinx et al, however, did reach significance when initial AAA diameter was included in their multivariate model 40…”
Section: Resultsmentioning
confidence: 88%
“…The quality appraisal attributed this study with medium bias risk. In 2 studies (1 medium and 1 high bias risk) no correlation was found in 91 follow‐up patients in total 9, 10. However, Satta et al did reach significance after 2 years of follow‐up 9…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…1 Increased MMP-9 levels were detected in plasma of AAA patients and patients with acute coronary syndromes. 2,3 In addition, aneurysm and atherosclerotic tissues overexpress MMP-1, -2, -3, -7, -8, -9, -12, -13, -14, and -17 (Carrell et al 4 and references therein).…”
mentioning
confidence: 99%